What Explains Boys’ Educational Underachievement in the Kingdom of Saudi Arabia? - Elsayed, Mahmoud A.A.; Clerkin, Aidan; Pitsia, Vasiliki; Aljabri, Nayyaf; Al-Harbi, Khaleel (World Bank, Washington, DC, 2022)
This paper examines the factors that are associated with boys’ underachievement in mathematics and science in Saudi Arabia, where students attend gender-segregated schools from grade 1 onward, as well as student achievement in these two subjects in grades 4 and 8 more generally. The paper employs data from two recent large-scale assessments of education: Trends in International Mathematics and Science Study 2019 and Saudi Arabia’s National Assessment of Learning Outcomes 2018. The results suggest that in grade 4, school climate was more strongly associated with boys' compared with girls' achievement in both mathematics and science, with boys attending schools of poorer school climate having a considerably lower performance compared with girls attending such schools. The findings also indicate that although greater literacy and numeracy readiness was linked with higher science achievement among boys and girls, grade 4 boys tended to benefit more from this readiness than girls. In addition, the results show that student absenteeism in grade 4 is particularly strongly associated with decreases in mathematics achievement among boys. In grade 8, interactions between student gender and students’ confidence in science, the degree of schools’ emphasis on academic success, and teachers’ age are observed. The paper concludes by discussing some of the implications of these findings for educators and policy makers in Saudi Arabia.